SUSTAINING THE SELF: EFL TEACHERS’ CONCEPTIONS AND PRACTICES OF WELL-BEING - Hamzah Puadi Ilyas; Wini Tarmini (Linguists : Journal of Linguistics and Language Teaching, 2026)
Teacher well-being is an essential foundation for effective language education, yet little is known about how experienced Indonesian EFL teachers understand and sustain their emotional and professional balance. This study addresses the question of how Indonesian EFL teachers conceptualize and maintain their well-being in relation to their classroom roles and daily practices. The research was conducted in senior high schools across seven urban areas in Indonesia, with 17 teachers aged 27 to 47. Data were collected through in-depth semi-structured interviews and reflective journals, and were analyzed using thematic analysis to identify patterns across participants’ accounts. The findings showed that teachers viewed well-being as grounded in meaningful teaching, positive relationships with students and colleagues, intentional classroom strategies that supported enjoyment and emotional steadiness, and cultural and spiritual values that strengthened their sense of purpose. Teachers also described institutional demands and administrative workload as threats to well-being, which they managed through boundary setting, selective task focus, and personal coping routines. The study concludes that teacher well-being emerges from the interplay of emotional fulfillment, social connection, pedagogical agency, and value-based reflection. The implications suggest that leaders and policymakers should prioritize supportive school cultures, reasonable workloads, and professional development that strengthens emotional awareness and reflective practice.